Energy optimization of a micro-CHP engine using 1-D and 3-D modeling. (5th June 2021) - Darzi, Mahdi; Zamani Meymian, Nima; Johnson, Derek
Highlights: An LPDI, NG, 2-stroke engine was modified to improve utilization factor for CHP. 1-D modeling and optimization focused on an improved exhaust resonator. Results from 1-D modeling improved delivery ratio and reduced fuel slip. 3-D CFD models led to an improved spark plug location based on charge stratification. Experiments using modeling results increased indicated efficiency from 25 to over 30% Abstract: This research focused on utilizing numerical simulation tools to improve the performance of a micro-CHP engine. The engine was developed at West Virginia University by screening candidate technologies and implementing those which were balanced between practicality and cost. The engine was a 34-cc, two-stroke engine which was modified to operate on low-pressure direct injection of natural gas combined with resonant intake and exhaust systems. This engine served as a baseline engine design. A 1-D simulation was developed and trained based on the baseline engine geometry and experimental data collected from laboratory experiments. After verifying the 1D model with measured data from the baseline configuration, a genetic algorithm approach was used to optimize the exhaust resonator design such that the fuel efficiency was maximized. Based on simulation outcomes, a new exhaust resonator was fabricated and tested. The experimental results showed an 8.3% improvement in brake thermal efficiency (BTE) compared to the baseline design. The test results of the optimized exhaust design were used in a 3-D CFD cold flow model to optimize the spark plug location to exploit charge stratification. The 3-D simulations suggested an alternative spark plug location, which was then applied on the engine and improved results were verified with additional experimental operation. The experimental results showed relative increase in BTE of 5.7% and a 4% decrease in total unburnt fuel compared to the original spark location.